Cytokine profiles and CD4 counts in HIV-positive individuals with cysticercosis: implications for sex-specific immune responses in co-endemic regions of Tanzania - Lema, Yakobo Leonard; Prodjinotho, Ulrich Fabien; Makasi, Charles; Nanyaro, Mary-Winnie A.; Kilale, Andrew Martin; Godfrey Mfinanga, Sayoki; Schmidt, Veronika; Carabin, Hélène; Winkler, Andrea Sylvia; Lyamuya, Eligius F.; Ngowi, Bernard James; Prazeres da Costa, Clarissa (Frontiers in Immunology, 2025)
IntroductionThe interplay between HIV and Taenia solium cysticercosis in co-endemic regions remains poorly understood, particularly regarding the immune responses but is relevant for an effective treatment strategy. This study aimed to investigate the relationship between peripheral cytokine profiles, CD4+ T-cell counts, and cysticercosis infection status in HIV-positive individuals in Tanzania’s southern highlands.MethodsWe conducted a cross-sectional study involving 110 HIV-positive individuals. Cysticercosis was diagnosed using antibody and antigen tests, with neurocysticercosis confirmed by CT imaging. CD4 counts and serum cytokine levels (pro- and anti-inflammatory) were analyzed using multivariate regression and MANOVA, including sex-stratified analyses.ResultsAmong participants, 20.9% tested positive for cysticercosis antibodies, 43.6% for antigens and 20.2% presented with brain cysts, with 10.6% showing active neurocysticercosis. Cysticercosis-positive individuals showed positive correlations between CD4 counts and pro-inflammatory cytokines (e.g., TNF-α, IL-1β), contrasting with negative correlations in cysticercosis-negative individuals. Sex-stratified analysis showed stronger regulatory cytokine responses in males compared to females, particularly involving higher levels of IL-10 and IL-4 indicating sex-specific immune modulation in co-infected individuals. However, overall cytokine profiles were not significantly influenced by CD4 categories or cysticercosis status.ConclusionThese results contribute to our understanding of immunological interactions in HIV-cysticercosis co-infection and underscore the need for further research with larger sample sizes to elucidate the clinical implications of these findings. Such studies could inform the development of more effective, sex-personalized treatment strategies for HIV patients in cysticercosis-endemic regions.